A novel combo‐transmission system of cold energy and electricity for aluminium profile production: Using liquid nitrogen and superconductor technologies. Issue 2 (26th December 2022) - Chen, Xiaoyuan; Li, Qiang; Jiang, Shan; Zhang, Mingshun; Fu, Lin; Shen, Boyang
Abstract: Aluminium production needs the most energy‐intensive technologies among all the metal processing sectors. During the process of aluminium profile extrusion, the whole production line needs bulk electricity, and the mold inside the extrusion equipment needs robust cold energy for rapid cooling of the metal surface. This paper presents a new combo‐transmission that can simultaneously deliver cold energy together with electricity to the aluminium profile extrusion line. Thanks to the superiority of virtually zero loss and compact size, the powerful superconducting cable is used to replace the conventional copper cable. The entire superconducting cable assembly is fully installed into a cryogenic pipeline and cooled by liquid nitrogen at 77 K. In addition to keeping a favourable cryogenic environment for the superconducting cable, liquid nitrogen can also provide a large amount of cold energy for cooling the metal surface. For a typical 100 MN aluminium extrusion production line, the design and optimization of 10 kA class superconducting cable with the pipeline cooling system for aluminium production are presented in detail. The simulation results and comparisons show that the total energy loss of superconducting transmission is about 46% of conventional copper cable, and the energy saved in a year can be up to about 240.6 MWh. Moreover, the net profit increases almost linearly along with the increases of the extrusion speed when the liquid nitrogen cooling is applied to the 100 MN production line. For the case of 23% increase in extrusion speed, the net profit can be up to 1.48 M$ in a year. Overall, the novel design, technical evaluation,  and economic analysis of the combo‐transmission system (cold energy + electricity) can provide a promising solution for future high‐dense aluminium production sectors. Abstract : A new combo‐transmission solution is proposed for enhancing both the energy efficiency and production benefit in an 100 MN aluminium extrusion workshop. The combo‐transmission scheme can transport the liquid‐nitrogen‐based cold energy and the superconductor‐based electric energy using the same cryogenic energy pipeline. The designed superconducting power cable has very superior performance regarding the compactness (83.6% smaller than the copper cable), and energy loss (54% smaller than the copper cable).